From participation to transformation: adolescents’ narratives of health and nutrition behavior change in a community-based project - Rastogi, Priyanshu; Rai, Raiza; Choudhary, Santosh; Kumar, Paramhans; Sharma, Shantanu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adolescent girls are vulnerable to malnutrition, anaemia, and infections due to a lack of awareness and availability of services, putting them at a high risk of poor health, nutrition, and hygiene status. Hence, community-based interventions need to be implemented to spread awareness using different behavior change models. This study aimed to assess participants’ awareness, perceptions, and experiences with health, nutrition, hygiene, and environmental initiatives implemented under the Jagriti program in rural and urban areas. Methods: Focus group discussions were conducted with adolescent girls. We performed thematic analysis to explore participants’ knowledge, practices, and feedback related to awareness campaigns, kitchen gardens, community-based events, digital interventions, and stakeholder meetings. Results: Participants showed awareness of anemia, menstrual hygiene, nutrition, sanitation, and early marriage. The establishment of kitchen gardens improved dietary diversity and supported livelihood. Traditional and culturally accepted methods such as nukkad natak, rangoli making, and folk-art improved community engagement and knowledge retention. The digital interventions provided health education, but with limitations such as shared phone access and gender disparities. In addition, village and stakeholder meetings discussed waste segregation, cleanliness and hygiene, and air pollution for disease prevention; however, attendance remained a challenge. Conclusions: The results emphasized the significance of multi-faceted, participatory strategies to increase awareness of health through cultural performances, digital interventions, and community involvement. Addressing barriers such as gender disparities, digital access limitations, and time constraints remains crucial to increasing the effectiveness of the program and its sustainability.